Cancellation of Death Penalty For Narcotics Producer In Human Rights Perspective - Setiodjati, Josef; Hamidi, Ayu (Indonesian Journal Publisher, 2025)
Death penalty is often associated with human rights violations, especially since the Amendment of the 1945 Constitution or the Indonesian Constitution Article 28 A which states that “Every person has the right to live and the right to defend his/her life and livelihood”. However, death penalty is needed to fulfill the people's sense of justice as a demand for security and tranquility. Death penalty can be a shock therapy for criminal offenders to create a deterrent effect as well as to create fear for the community so that people do not commit acts that are punishable by death penalty, especially narcotics crimes. The Supreme Court (MA) as an Indonesian judicial institution has annulled the death penalty for narcotics factory owner Hanky Gunawan. In the Judicial Review (PK) decision, Hanky was only sentenced to 15 years in prison on the grounds that the death penalty violated the constitution. This certainly raises the pros and cons related to the direction of Indonesia's law enforcement system in the future